2013
DOI: 10.1371/journal.pone.0056691
|View full text |Cite|
|
Sign up to set email alerts
|

Akt and c-Myc Induce Stem-Cell Markers in Mature Primary p53−/− Astrocytes and Render These Cells Gliomagenic in the Brain of Immunocompetent Mice

Abstract: Astrocytomas and their most malignant variant glioblastoma multiforme (GBM) represent the vast majority of primary brain tumors. Despite the current progress in neurosurgery, radiation therapy and chemotherapy, most astrocytomas remain fatal disorders. Although brain tumor biology is a matter of intense research, the cell-of-origin and the complete astrocytoma-inducing signaling pathway remain unknown. To further identify the mechanisms leading to gliomagenesis, we transduced primary astrocytes on a p53−/− bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 55 publications
3
27
0
Order By: Relevance
“…Gradually, successive interplay of differentiation and de-differentiation aid the transformation of radial astrocytic stem cells into neuron of hippocampal region via respective transformation to type 1 to type 2 to type 3 neural stem cells, while the ependymal cells lining the region of cerebrospinal fluid are under the crucial influence of various growth factors and their intricate signaling system such as Notch, Wnt, TGF-β, BMP, etc [61,62] . Periventricular adult NSC has been characterized to express a high level of GFAP-positive astrocytes, which along with combined loss of tumor suppressors p16 and p19 (causing increased expression of eGFr) and loss of p53 (causing over-expression of oncogenes such as c-myc) clearly indicate the de-differentiated property of astrocytes to give origin to GBM [63][64][65] . Parallel to these modifications, the formation of type C progenitor cells from SvZ, which later become restricted to neuroblast and oligodendrocyte precursor cells (OPC), seem to inculcate a number of genetic alterations to manifest initial gliomagenesis [66,67] .…”
mentioning
confidence: 99%
“…Gradually, successive interplay of differentiation and de-differentiation aid the transformation of radial astrocytic stem cells into neuron of hippocampal region via respective transformation to type 1 to type 2 to type 3 neural stem cells, while the ependymal cells lining the region of cerebrospinal fluid are under the crucial influence of various growth factors and their intricate signaling system such as Notch, Wnt, TGF-β, BMP, etc [61,62] . Periventricular adult NSC has been characterized to express a high level of GFAP-positive astrocytes, which along with combined loss of tumor suppressors p16 and p19 (causing increased expression of eGFr) and loss of p53 (causing over-expression of oncogenes such as c-myc) clearly indicate the de-differentiated property of astrocytes to give origin to GBM [63][64][65] . Parallel to these modifications, the formation of type C progenitor cells from SvZ, which later become restricted to neuroblast and oligodendrocyte precursor cells (OPC), seem to inculcate a number of genetic alterations to manifest initial gliomagenesis [66,67] .…”
mentioning
confidence: 99%
“…By combining activation of specific oncogenes and loss of tumor suppressor genes, it is possible to induce GBM from cortical astrocytes [56]. Examples are the combination of p16(INK4a)-p19(ARF) loss with K-Ras and Akt activation [57], p16(INK4a) and p19(ARF) loss with EGFR activation [58] and p53 loss with myr-Akt and cMyc overexpression in mature astrocytes [59]. Basically, the capacity of transformation inversely correlates with differentiation.…”
Section: The Glioma Origin and The Stem Cell Theorymentioning
confidence: 99%
“…Recent studies have shown that brain tumors can arise both from differentiated cells (Friedmann-Morvinski et al 2012;Radke et al 2013) and from the cancer stem-like cells (Chen et al 2012). In some GBM patients, a spatial relationship between the tumor location and the neural stem cell niche is observed, while in other patients this association does not exist (Lim et al 2007).…”
Section: Niche-stem Cells and Adhesion Of Tumor Cellsmentioning
confidence: 99%